HUBUNGAN KAPASITAS PETANI DENGAN KEBERLANJUTAN USAHA PETANI TANAMAN HIAS DI KELURAHAN BENDE KECAMATAN KADIA KOTA KENDARI - Muhamad Rafil; Dasmin Sidu; Salahuddin Salahuddin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
The purpose of this study was to determine the capacity of farmers and business sustainability in ornamental plant business and to determine the relationship between farmer capacity and business sustainability of ornamental plant farmers in Bende Village, Kadia District, Kendari City. The determination of the research location was carried out purposively with the consideration that the research location was a center for ornamental plants in Kendari City. The sample in this study was 22 farmers who were taken by the census method. Data collection by way of interviews, surveys, and documentation and using a questionnaire as a data collection instrument. Data analysis used the class interval formula and Spearman rank correlation with the help of SPSS 26. The results of this study indicate that the capacity of ornamental plant farmers in Bende Sub-district which consists of social capacity is dominantly determined by the ability to build partnership networks with a percentage of 45.45%, managerial capacity, dominance is determined by the ability to communicate in problem-solving with a percentage of 54.55% and technical capacity, dominant is determined by the ability to carry out plant nurseries with a percentage of 45.45%. Business continuity in Bende Village consists of social sustainability, dominantly determined by education level with a percentage of 63.63%, economic sustainability, dominantly determined by marketing ability with a percentage of 45.45% and environmental sustainability, dominantly determined by the ability to keep the business environment clean with a percentage of 54 .55%. There is a close and significant relationship between farmer capacity and business sustainability with a correlation coefficient of 0.711 with a significant level of 0.000.